A Retrospective Cohort Study comparing Retention and Viral suppression between Co-morbidity Adherence Clubs and HIV-Only Adherence Clubs in Cape Town, South Africa - Allerton, Joanna (Department of Public Health and Family Medicine, 2019)
In South Africa, there is an increasing population of those with both Human Immunodeficiency Virus (HIV) and one or more non-communicable diseases (NCDs). This is thought to be due to a number of factors, including both the successful Antiretroviral Therapy (ART) programme (which has increased the life-expectancy of those with HIV) and the increasing prevalence of NCDs (due to an aging population, lifestyle changes and urbanisation). This co-morbid population has been shown have poor health outcomes especially in terms of adherence (due to pill burden, multiple appointments etc). There are currently very few models of integrated care for those with both HIV and NCDs, despite well-documented potential benefits of this approach for both the patient and the health system (in terms of efficiency). One such model of care, the co-morbidity adherence clubs (for those with both HIV and hypertension and/or diabetes), was implemented in 2016 in South Africa and this study aims to compare the key outcomes of retention and viral suppression between these clubs and the established HIV-only adherence clubs. Part A is the study protocol which lays the foundation for the need for this research, and explains how the research will be conducted. Part B forms the literature review which gives a summary of the existing literature and provides context for the dissertation. Part C is the manuscript, presenting the analysis of the retrospective cohort study, and includes a discussion on the implications of key findings. The study sample comprised 602 HIV-positive adults (501 from the HIV-only club model and 101 from the co-morbidity club model). The overall female proportion was 70.3% and the median age was 38 years. The results showed that there was no difference in the proportion of those retained (84.2% vs 85.6%, p=0.703) or the proportion who were virally suppressed (97% vs 97%, p=0.999) in the co-morbidity club compared to the HIV-only club. In multivariable logistic regression models, adjusted for age, sex and duration on ART, there was no significant difference in retention (adjusted odds ratio [aOR] 0.75 95% confidence interval [CI] 0.38, 1.47) or viral suppression (aOR 0.98 95% CI 0.23, 4.14) by club model. The most common reason for loss of retention from the HIV-only club was non-attendance whereas for the co-morbidity club it was being sent back to clinic for high blood pressure. This study provides early evidence of comparable short-term patient outcomes between HIV-only and co-morbidity club models and provides reassurance that co-morbidity clubs can be implemented without affecting the outcomes of HIV care. It also provides early promise that, whilst the differential reasons for loss of retention by club model merit further investigation, patients with HIV and hypertension and/or diabetes can safely be managed in co-morbidity clubs.